THE EFFECT OF FIRM GROWTH, DIVIDEND POLICY, FIRM SIZE, AND LEVERAGE ON PROFIT QUALITY (Study On Transportation Companies Listed On The Indonesia Stock Exchange) - Reza Hendri Yana; Ghazali Syamni; Nurlela; Chairil Akhyar; Sari Yulis Terfiadi (PT. Radja Intercontinental Publishing, 2024)
This study aims to determine how the influence of firm growth, dividend policy, firm size, and leverage on profit quality in transportation companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The quality of profit in this study is measured by comparing the value of operating cash flows with net income, then the firms’s growth is measured using the results of the current year's total assets minus the previous year's total assets and divided by the previous year's total assets. Meanwhile, dividend policy is measured by comparing cash dividends to net income, and firm size is measured using the natural logarithm of total equity, and variable leverage is measured by comparing total debt with total company equity. This study uses secondary data obtained from each financial statement of transportation companies listed on the Indonesia Stock Exchange.The sample used in this study is as many as 20 companies obtained using purposive sampling techniques, where the data analysis method used is a multiple linear regression test using the help of eviews software version 10. The research findings indicate that partial company growth has a non-significant positive effect on earnings quality, whereas dividend policy and company size partially have a significant positive effect on earnings quality. Meanwhile, leverage partially has a significant negative effect on earnings quality in transportation companies listed on the Indonesia Stock Exchange for the period 2018-2022.